Bentuk Dukungan Sosial Masyarakat Pada Pendidikan Tinggi Bagi Anak Perempuan di Desa Sei Limbat, Kecamatan Selesai, Kabupaten Langkat - Andini Kartika Sari Andini; Mia Aulina Lubis; Berlianti (Talenta usu, 2023)
Education is needed for all people including women. However, the reality is that there are still many girls who are hindered from continuing their higher education because of traditional thoughts, such as choosing to get married or work after graduating from high school. This research was conducted in Desa Sei Limbat, Kecamatan Selesai, Kabupaten Langkat using eight informants consisting of one key informant, four main informants and three additional informants. Data collection techniques using qualitative methods with interviews, observation and documentation. So that in the end it can be concluded from the results of this study. The results of the study show that the form of social support needed by girls tends to be emotional support that comes from the family. Furthermore, instrumental support, appreciation, informative, and social networks go hand in hand after providing emotional support. With the existence of social support from the community, of course there are supporting factors that are more directed at the feeling of empathy given to girls' education. While the inhibiting factors are attitudes that are contrary to norms and humanity. Keywords: Social support, higher education, supporting and inhibiting factors, sources of social support